Prognostic Significance of COX-2 Overexpression in BRAF-Mutated Middle Eastern Papillary Thyroid Carcinoma - Parvathareddy, Sandeep Kumar (Int J Mol Sci, 2020)
The cyclooxygenase-2 (COX-2)–prostaglandin E2 (PGE2) pathway has been implicated in carcinogenesis, with BRAF mutation shown to promote PGE2 synthesis. This study was conducted to evaluate COX-2 expression in a large cohort of Middle Eastern papillary thyroid carcinoma (PTC), and further evaluate the prognostic significance of COX-2 expression in strata of BRAF mutation status. BRAF mutation analysis was performed using Sanger sequencing, and COX-2 expression was evaluated immunohistochemically using tissue microarray (TMA). COX-2 overexpression, noted in 43.2% (567/1314) of cases, was significantly associated with poor prognostic markers such as extra-thyroidal extension, lymph-node metastasis, and higher tumor stage. COX-2 was also an independent predictor of poor disease-free survival (DFS). Most notably, the association of COX-2 expression with DFS differed by BRAF mutation status. COX-2 overexpression was associated with poor DFS in BRAF-mutant but not BRAF wild-type PTCs, with a multivariate-adjusted hazard ratio of 2.10 (95% CI = 1.52–2.92; p < 0.0001) for COX-2 overexpressed tumors in BRAF-mutant PTC. In conclusion, the current study shows that COX-2 plays a key role in prognosis of PTC patients, especially in BRAF-mutated tumors. Our data suggest the potential therapeutic role of COX-2 inhibition in patients with BRAF-mutated PTC.